Does Acute Side-alternating Vibration Exercise Enhance Ballistic Upper-body Power? - Cochrane, D. J.; Black, M. J.; Barnes, M. J. (International Journal of Sports Medicine, 2014)
The aim of this study was to investigate the effects of acute vibration exercise, at 2 different frequencies, on upper body power output. Muscle activity (EMG) and upper-body peak power was measured in 12 healthy males during ballistic bench press throws at 30% of 1-repetition maximum on a Smith machine. Measures were made prior to, 30 s and 5 min after one of 3 conditions performed for 30 s in a press-up position: side-alternating vibration at 20 Hz, 26 Hz and no vibration. EMG was recorded in the anterior deltoid, triceps brachii and pectoralis major during ballistic bench press throws as well as during application of each condition. While peak power output was higher at 5 min post condition across all conditions, compared to baseline measures (P<0.05), only 20 Hz vibration resulted in a significant increase in peak power output (P<0.05) compared to no vibration. EMG was greater during both vibration conditions, compared to no vibration (P<0.001). However, this difference was not evident during bench press throws when no difference was seen in muscle activity between conditions. These findings suggest that 20 Hz vibration has an ergogenic effect on upper-body power that may be due to peripheral, rather than central, mediated mechanisms.
Keywords: post-activation potentiation; muscle performance; electromyography